2022
DOI: 10.1002/hbm.25797
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between audiovisual temporal synchrony and semantic congruency in the cross‐modal boost of the visual target discrimination during the attentional blink

Abstract: The visual attentional blink can be substantially reduced by delivering a task‐irrelevant sound synchronously with the second visual target (T2), and this effect is further modulated by the semantic congruency between the sound and T2. However, whether the cross‐modal benefit originates from audiovisual interactions or sound‐induced alertness remains controversial, and whether the semantic congruency effect is contingent on audiovisual temporal synchrony needs further investigation. The current study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 84 publications
7
18
1
Order By: Relevance
“…Follow-up ttests showed that responses were significantly faster in the simultaneous VA condition than in the remaining three conditions [V + A + SIM vs. V + : t( 29 . These data indicate that presenting semantically congruent sounds simultaneously with visual targets brought the greatest information redundancy and thus resulted in a behavioral gain even when the sounds were task-irrelevant, consistent with the literature (e.g., Zhao et al, 2022;Zimmer, Itthipanyanan, et al, 2010;Zimmer, Roberts, et al, 2010). The hit rate collapsed across target types was above 95%, and no significant main effect of target type was found, although the Bayes factor did not provide substantial evidence for the null hypothesis [F(3, 87) = 2.378, p = .075, η 2 p = 0.076, BF 10 = 0.636; V + A + SIM : 95.93 ± 0.59%; V + A + D100 : 97.10 ± 0.51%; V + A + D300 : 96.11 ± 0.58%; V + : 95.93 ± 0.57%].…”
Section: Behavioral Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Follow-up ttests showed that responses were significantly faster in the simultaneous VA condition than in the remaining three conditions [V + A + SIM vs. V + : t( 29 . These data indicate that presenting semantically congruent sounds simultaneously with visual targets brought the greatest information redundancy and thus resulted in a behavioral gain even when the sounds were task-irrelevant, consistent with the literature (e.g., Zhao et al, 2022;Zimmer, Itthipanyanan, et al, 2010;Zimmer, Roberts, et al, 2010). The hit rate collapsed across target types was above 95%, and no significant main effect of target type was found, although the Bayes factor did not provide substantial evidence for the null hypothesis [F(3, 87) = 2.378, p = .075, η 2 p = 0.076, BF 10 = 0.636; V + A + SIM : 95.93 ± 0.59%; V + A + D100 : 97.10 ± 0.51%; V + A + D300 : 96.11 ± 0.58%; V + : 95.93 ± 0.57%].…”
Section: Behavioral Resultssupporting
confidence: 88%
“…Follow‐up t ‐tests showed that responses were significantly faster in the simultaneous VA condition than in the remaining three conditions [V + A + SIM vs. V + : t (29) = −3.201, p FDR = 0.010, Cohen's d = −0.584, BF 10 = 11.620; V + A + SIM vs. V + A + D100 : t (29) = −2.909, p FDR = 0.014, d = −0.531, BF 10 = 6.180; V + A + SIM vs. V + A + D300 : t (29) = −3.987, p FDR = 0.002, d = −0.728, BF 10 = 72.395], whereas the remaining three conditions did not differ substantially [V + A + D100 vs. V + : t (29) = −0.325, p FDR = 0.747, d = −0.059, BF 10 = 0.204; V + A + D100 vs. V + A + D300 : t (29) = −1.442, p FDR = 0.240, d = −0.263, BF 10 = 0.494; V + A + D300 vs. V + : t (29) = 1.103, p FDR = 0.335, d = 0.201, BF 10 = 0.338]. These data indicate that presenting semantically congruent sounds simultaneously with visual targets brought the greatest information redundancy and thus resulted in a behavioral gain even when the sounds were task‐irrelevant, consistent with the literature (e.g., Zhao et al., 2022; Zimmer, Itthipanyanan, et al., 2010; Zimmer, Roberts, et al., 2010). The hit rate collapsed across target types was above 95%, and no significant main effect of target type was found, although the Bayes factor did not provide substantial evidence for the null hypothesis [ F (3, 87) = 2.378, p = .075, η 2 p = 0.076, BF 10 = 0.636; V + A + SIM : 95.93 ± 0.59%; V + A + D100 : 97.10 ± 0.51%; V + A + D300 : 96.11 ± 0.58%; V + : 95.93 ± 0.57%].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Electroencephalographic (EEG) signals were continuously recorded with a NeuroScan SynAmp amplifier (NeuroScan, Inc., El Paso, TX, USA) and a custom-built 64-electrode elastic cap on which the electrodes were positioned in accordance with a modified 10-10 system montage (for details, see [ 39 ]). Two additional electrodes, AFz and M1 (left mastoid), served as the ground and reference electrodes, respectively, for online EEG recording.…”
Section: Methodsmentioning
confidence: 99%
“…The elimination of ABs is currently an important topic in the research on attention. A growing body of research has found that an AB is improved when auditory stimulation accompanies the experiment [9][10][11][12][13][14]. However, in focusing on the auditory improvement of ABs, these studies failed to further explore the effects of auditory stimulus material representations on ABs.…”
Section: Introductionmentioning
confidence: 99%